Formulation and Physicochemical Evaluation of Lab-Based Aloe adigratana Reynolds Shampoos. (4th April 2020) - Sbhatu, Desta Berhe; Berhe, Goitom Gebreyohannes; Hndeya, Abadi Gebreyesus; Abraha, Haftom Baraki; Abdu, Asmael; Gebru, Haftay Abadi; Taye, Molla Gereme; Mulugeta, Afework; Weldemichael, Micheale Yifter; Tekle, Hailekiros Tadesse; Kidanemariam, Haileselassie Gebremeskel
Abstract : Aloe L. species (Aloaceae) are ethnobotanically very valuable plants in many communities and civilizations. Nonetheless, very few species are extensively studied to explore their applications in the pharmaceutical and medical, cosmetic and personal care, food and beverage, and detergent industries. This study evaluated the characteristics and quality of lab-based shampoos formulated from the gel of Aloe adigratana Reynolds. Five shampoo formulations, 20 mL each, were prepared from A. adigratana gel in combination with one to two drops of coconut oil, jojoba oil, olive oil, pure glycerin oil, lemon juice, and vitamin E. Gel mass is prepared from mature, healthy leaves collected from the natural stand. The phytochemistry of the gel of the plant was also studied using phytochemical screening, proximate composition, and GC-MS analysis studies. Shampoo formulations with higher proportion (40 to 50% v/v) of A. adigratana gel were found to have comparable characteristics and qualities with a marketed shampoo. They fall within the range of acceptable quality parameters of commercial shampoos. The phytochemical studies of A. adigratana gel showed that the plant is the source of highly valued compounds for the preparation of shampoos. The gel was found to be rich in saponins as well as dodecanoic acid, hexadecanoic acid, and phytol. Future works should focus in the development of refined protocol towards formulating A. adigratana -based shampoos.